Ears - Gleisner, Jenna Lee (Jump, 2020)
"Ears introduces emergent readers to unique animal ear features while providing them with a supportive first nonfiction reading experience. Carefully crafted text uses high-frequency words, repetitive sentence patterns, and strong visual references to support emergent readers, making sure they aren't facing too many challenges at once."--
"Tadpole books are published by Jump!"
Includes index.
Age 3-6.
Keywords: Ear -- Juvenile literature